Strong influence of the oxygen stoichiometry on the vortex bundle size and critical current densities J c of GdBa2Cu3Ox -coated conductors grown by co-evaporation - Haberkorn, N.; Guimpel, J.; Suárez, S.; Troiani, H.E.; Granell, P.; Golmar, F.; Lee, J.-H.; Moon, S.H.; Lee, H.; Haberkorn, Néstor; Guimpel, Julio (IOP Publishing, 2017)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas